PENGENALAAN ALAT TANGKAP IKAN YANG RAMAH LINGKUNGAN UNTUK MENJAGA KELESTARIAN HAYATI BIOTA DI DESA CEMARA - Dwiyanti, Septiana; Setyono, Bagus Dwi Hari; Alim, Sahrul; Scabra, Andre Rachmat; Asri, Yuliana (Jurnal Pepadu, 2024)
Fishing is not only about efforts to meet food needs and livelihoods but has become more complex involving socio-economic issues and environmental sustainability. There needs to be more attention to fishing activities to ensure their sustainability. By introducing environmentally friendly fishing gear to children in Cemara village, Lembar District, it is hoped that these young participants, as the future generation, will be more aware of and care for the preservation of the biological environment around them. This activity involved 30 children aged 10-12 years. The Community Service Activity (PKM) was held on June 5, 2024, from 3:00 PM until completion in Cemara Village, Lembar District, West Lombok Regency. This activity was conducted using a counseling method with an approach to the children. The method of this activity started with a participatory approach, field demonstrations, information sharing, collaboration, and monitoring and evaluation. The results of the counseling on the use of environmentally friendly fishing gear in Cemara village showed that the participants were very enthusiastic about this activity, as evidenced by the number of questions from the participants. The atmosphere of this counseling activity was pleasant and friendly. Based on the discussion results, it was found that the counseling participants knew many types of fishing gear but did not know much about whether the fishing gear was environmentally friendly or not. The conclusion of the community service activity carried out in Cemara village, Lembar District, is that this activity has increased the participants' knowledge and information about environmentally friendly fishing gear, as shown by the many questions and active participation of the participants.